1996
DOI: 10.1258/0956462961918563
|View full text |Cite
|
Sign up to set email alerts
|

Response to hepatitis B vaccination in a primary care setting: influence of HIV infection, CD4+ lymphocyte count and vaccination schedule

Abstract: Factors affecting the response to hepatitis B vaccination in a primary care setting were examined by means of a review of case notes of patients attending 22 sexually transmissible disease services. Where not available from the notes, presence of antibody to hepatitis B surface antigen (anti-HBs) was determined by testing available stored serum. One hundred and ninety-five patients completed a course of 3 injections and had an anti-HBs assay performed. The highest response rate (anti-HBs > or = 10 IU/L) was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 0 publications
3
39
0
3
Order By: Relevance
“…The association of HBV seroprotection rates and CD4 counts is controversial. Some studies have shown higher response rates associated with higher CD4 counts while others have obtained contrary data [15,16,18,19,[22][23][24][25]. Our study showed that CD4 counts had no influence on the immune response to HBV vaccination and accords with Wilson [16] and Overton [22] studies.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The association of HBV seroprotection rates and CD4 counts is controversial. Some studies have shown higher response rates associated with higher CD4 counts while others have obtained contrary data [15,16,18,19,[22][23][24][25]. Our study showed that CD4 counts had no influence on the immune response to HBV vaccination and accords with Wilson [16] and Overton [22] studies.…”
Section: Discussionsupporting
confidence: 82%
“…Prior studies of the immune responses to HBV vaccine in HIV infected patients have indicated varying response rates from 0% to 87%. [15,16,18,19,[22][23][24][25]. Cornejo-Juárez et al [26] found 60.7% response rate in HIVinfected patients vaccinated with HBV recombinant vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…The 0, 1 and 6 months and the 0, 1 and 2 months, with an additional dose at 12 months schedules have both been shown to be efficacious in HIV-infected patients [18,19]. There are very few data on the 0, 7-10 and 21 days, with an additional dose at 12 months schedule in HIV-positive patients, although one small study showed a 51% response after the first three doses and an 88% response after six doses [20].…”
Section: Immunizationmentioning
confidence: 99%
“…Immunization for hepatitis B in HIV-infected CKD patients is more important because not only does HBV infection occur more frequently with HIV infection for behavioral reasons, but also because the pre-HAART studies suggested that these patients are more likely to develop chronic infection [105]. However, several reports have suggested that antibody response to hepatitis vaccination is impaired in HIV-infected patients [106, 107, 108]. Although hepatitis vaccination may increase plasma viral load, the effect is minimal and transient and is unlikely to be of clinical relevance [109, 110].…”
Section: Vaccinationmentioning
confidence: 99%